2016
DOI: 10.1016/j.camwa.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A well-balanced scheme for the shallow-water equations with topography

Abstract: International audienceA non-negativity preserving and well-balanced scheme that exactly preserves all the smooth steady states of the shallow water system, including the moving ones, is proposed. In addition, the scheme must deal with vanishing water heights and transitions between wet and dry areas. A Godunov-type method is derived by using a relevant average of the source terms within the scheme, in order to enforce the required well-balance property. A second-order well-balanced MUSCL extension is also desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 49 publications
1
82
0
Order By: Relevance
“…We consider the well-balanced numerical scheme for the shallow-water equations with topography introduced in [8] and its second-order well-balanced extension, which requires two heuristic parameters. The goal of the present contribution is to derive a parameter-free second-order well-balanced scheme.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We consider the well-balanced numerical scheme for the shallow-water equations with topography introduced in [8] and its second-order well-balanced extension, which requires two heuristic parameters. The goal of the present contribution is to derive a parameter-free second-order well-balanced scheme.…”
Section: Introductionmentioning
confidence: 99%
“…schemes that exactly preserve such steady solutions, have been derived in the last decade (see for instance [2,4,5,8]). Namely, in [8], the authors suggested a well-balanced Godunov-type scheme based on a two-state approximate Riemann solver. We briefly recall the general form of a numerical scheme that falls within this classification (see for instance [10]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations